Autogenous demineralized dentin matrix for tissue engineering applications: Radiographic and histomorphometric studies - Gomes, M. F.; dos Anjos, MJD; Nogueira, T. D.; Guimaraes, SAC (Quintessence Publishing Co Inc, 2002)
Purpose: This work evaluated the osteoconductive properties of autogenous demineralized dentin matrix (ADDM) on surgical bone defects in the parietal bone of rabbits, using the guided bone regeneration technique and polytetrafluoroethylene (PTFE) membrane. Materials and Methods: Surgical bone defects were created in 24 adult rabbits and repaired with either ADDM and PTFE (experimental group) or PTFE alone (control group). The ADDM had been obtained from the central incisors of the experimental rabbits. The rabbits were sacrificed after 15, 30, 60, and 90 days and the defects examined radiographically and histologically. Results: Radiographically, the defects in the experimental animals achieved radiopacity more quickly than the defects in the control group. Discussion: After 15, 30, 60, and 90 days of observation following surgery, the ADDM slices appeared to stimulate new bone formation. The dentin slices were completely incorporated into the new bone tissue and were resorbed during the bone repair. Conclusions: Bone repair was accelerated on the bone defects treated with ADDM when compared to the control group.
Keywords: autogenous demineralized dentin matrix; bone repair; guided bone regeneration; polytetrafluoroethylene membrane